Real time, in-situ deuteriding of uranium encapsulated in grout; effects of temperature on the uranium-deuterium reaction. (October 2017) - Stitt, C.A.; Paraskevoulakos, C.; Harker, N.J.; Banos, A.; Hallam, K.R.; Jones, C.P.; Scott, T.B.
Graphical abstract: Highlights: In-situ, time dependent examination of the uranium-deuterium reaction in grout. X-Ray powder diffraction and tomography were used to investigate deuteride formation. Low metal and grout thermal conductivities significantly limited deuteride formation. The metal temperature may be more influential to deuteride formation than the gas. Strong bonding was observed between the uranium oxide and grout. Abstract: To accurately predict the initiation and evolution of uranium hydride potentially present in nuclear waste containers, studies of simulated conditions are required. Here, for the first time, the uranium-deuterium reaction was examined in-situ, in real time, whilst within grouted media. A deuterium gas control rig and stainless steel-quartz glass reaction cell were configured on a synchrotron beam line to collect X-ray diffraction and X-ray tomography data. It was found that deuteride formation was limited by the uranium and grout thermal conductivities and deuteride initiation only commenced above a threshold temperature. Strong adherence between uranium oxide and grout was also observed.